2020
DOI: 10.1007/s00702-020-02258-z
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune encephalitis with psychiatric features in adults: historical evolution and prospective challenge

Abstract: Our review aims to delineate the psychiatric spectrum of autoantibody-associated autoimmune encephalitis over time through its discoveries of antibodies. We searched in PubMed for appropriate articles depicting the first appearance and spectrum of psychiatric symptomatology in autoantibody-positive encephalitis for this narrative review. Memory impairment was first associated with autoantibodies against intracellular antigens such as anti-HuD antibodies in 1993. 8 years later, autoantibodies against cell membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 117 publications
0
12
0
5
Order By: Relevance
“…A prospective study of the reliability of the ACES score is necessary. The study by Hansen et al ( 35 ) showed that there are various manifestations of psychiatric symptoms in AE. Given that the behavior is a broad term, it is important to develop a better scoring system that includes different aspects of psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of the reliability of the ACES score is necessary. The study by Hansen et al ( 35 ) showed that there are various manifestations of psychiatric symptoms in AE. Given that the behavior is a broad term, it is important to develop a better scoring system that includes different aspects of psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…1 Patients with autoimmune encephalitis may also have psychologic features such as anxiety, depression, mood dysfunction, and hallucinations. 7 Imaging findings for autoimmune encephalitis are variable and can range from none at all to a markedly abnormal examination with symptoms including cranial neuropathies, dystonia, chorea, psychosis, or seizures. 6 Signal changes may affect the white matter, cortex, deep gray nuclei, and brain stem.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Although psychiatric symptomatology can occur with any antibody-positive encephalitis, it is more frequent in presentations associated with autoantibodies targeting extracellular antigens. 11…”
Section: Autoimmune Encephalitis and Autoantibody Subtypesmentioning
confidence: 99%
“…These antibodies most likely act through T-cell mechanisms and are associated with psychosis. 11,21,22 antibodies are very strongly associated with breast cancer in women. These antibodies target intracellular proteins important for recycling synaptic vesicles.…”
Section: Autoantibodies Targeting Intracellular Antigens and Proteinsmentioning
confidence: 99%